2010
DOI: 10.1136/hrt.2010.194563
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of glucose-insulin-potassium and insulin-glucose as adjunctive therapy in acute myocardial infarction: a contemporary meta-analysis of randomised controlled trials

Abstract: Current evidence suggests that GIK with insulin does not reduce mortality in patients with AMI. However, studies of glycaemia are inconclusive and it remains possible that glycaemic control is beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 37 publications
0
30
1
4
Order By: Relevance
“…[84][85][86] A 2010 meta-analysis of 9 randomized trials that involved >28 000 patients did not reveal any mortality benefit with GIK therapy in ST-segment-elevation AMI. 87 However, all the studies examined AMI patients ≥3 hours after the onset of symptoms except for Glucose-InsulinPotassium Study-1 (GIPS-1), which accounted for only 3% of the total population in the meta-analysis and had a relative risk of 0.83, whereas 70% of the meta-analysis population (>20 000 patients) were from 1 large trial, the Clinical Trial of Reviparin and Metabolic Modulation in Acute Myocardial Infarction Treatment Evaluation-Estudios Cardiologicos Latino America (CREATE-ECLA), in which the mean delay time was 4.7 hours. 87 In contrast, the recently completed IMMEDIATE trial showed benefit when GIK was instituted very early in the course of ACS as in the large-animal coronary ligation studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[84][85][86] A 2010 meta-analysis of 9 randomized trials that involved >28 000 patients did not reveal any mortality benefit with GIK therapy in ST-segment-elevation AMI. 87 However, all the studies examined AMI patients ≥3 hours after the onset of symptoms except for Glucose-InsulinPotassium Study-1 (GIPS-1), which accounted for only 3% of the total population in the meta-analysis and had a relative risk of 0.83, whereas 70% of the meta-analysis population (>20 000 patients) were from 1 large trial, the Clinical Trial of Reviparin and Metabolic Modulation in Acute Myocardial Infarction Treatment Evaluation-Estudios Cardiologicos Latino America (CREATE-ECLA), in which the mean delay time was 4.7 hours. 87 In contrast, the recently completed IMMEDIATE trial showed benefit when GIK was instituted very early in the course of ACS as in the large-animal coronary ligation studies.…”
Section: Discussionmentioning
confidence: 99%
“…87 However, all the studies examined AMI patients ≥3 hours after the onset of symptoms except for Glucose-InsulinPotassium Study-1 (GIPS-1), which accounted for only 3% of the total population in the meta-analysis and had a relative risk of 0.83, whereas 70% of the meta-analysis population (>20 000 patients) were from 1 large trial, the Clinical Trial of Reviparin and Metabolic Modulation in Acute Myocardial Infarction Treatment Evaluation-Estudios Cardiologicos Latino America (CREATE-ECLA), in which the mean delay time was 4.7 hours. 87 In contrast, the recently completed IMMEDIATE trial showed benefit when GIK was instituted very early in the course of ACS as in the large-animal coronary ligation studies. 10,11 Paramedics using ECG-based decision support gave GIK treatment in the ambulance at a median of 90 minutes after ischemic symptom onset to 871 patients in this randomized, placebo-controlled, double-blind effectiveness trial on patients with ACS in 13 US cities.…”
Section: Discussionmentioning
confidence: 99%
“…Łączna analiza danych z 3 badań potwierdziła, że wlew insuliny i glukozy nie spowodował zmniejszenia śmiertelności w przypadku braku kontroli glikemii u chorych z ostrym MI i cukrzycą (ryzyko względne 1,07; 95% CI 0,85-1,36; p = 0,547) [331]. Ponieważ ani w badaniu DIGAMI 2, ani w badaniu HI-5 nie uzyskano różnicy w zakresie kontroli glikemii między grupami leczonymi intensywnie i grupami kontrolnymi, nadal pozostaje otwartą kwestią, czy obniżanie glikemii jest korzystne.…”
Section: S 359unclassified
“…Insulin is recognized as the central component of the GIK cocktail; glucose and potassium are added to adjust for the secondary effects of glycemic alteration and hypokalemia caused by simultaneous cellular uptake of potassium with glucose. Although evidence for the clinical benefit of GIK has been mixed, [33][34][35][36][37] …”
Section: Cardioprotective Effects Of Insulinmentioning
confidence: 99%